FROM EXCLUSION TO INCLUSION: THE ROLE OF FINANCIAL TECHNOLOGY IN ENHANCING SUSTAINABILITY PERFORMANCE IN INDONESIAN MUSLIM MSMEs - Apia Dewi Agustin; Muhammad Hanif Ibrahim (Laboratorium Riset Ekonomi, 2024)
Purposes: This study aims to reveal the impact of financial technology (FinTech) in enhancing the sustainability performance of Indonesian Muslim Micro, Small, and Medium Enterprises (MSMEs). Furthermore, this study also investigates the mediating roles of financial literacy, financial accessibility, competitiveness, and green innovation, and the moderating effects of Sustainable Development Goals (SDGs) consciousness and religiosity on the relationships between these mediators and the sustainability performance of Muslim MSMEs. Methods: Data were collected from 179 Indonesian Muslim MSMEs. And analyzed using Structural Equation Modeling (SEM) using quantitative aproach. Results: By the objectives, the results reveal that FinTech adoption positively impacts the sustainability performance of Indonesian Muslim MSMEs. Financial literacy, financial accessibility, SDGs knowledge enhancing the overall effect of FinTech on sustainability performance. Furthermore, religiosity significantly moderates these relationships, with higher levels of these moderators strengthening the positive impacts. Conclusion and suggestion: This study underscores the critical role of FinTech in advancing sustainable performance among Indonesian Muslim MSMEs. By enhancing financial literacy, financial accessibility, competitiveness, and green innovation, FinTech can substantially improve sustainability outcomes. Additionally, integrating SDG consciousness and religiosity into MSME practices can further strengthen these positive impacts. Policymakers and practitioners should account for these factors, particularly within the Islamic context, when developing strategies to support the sustainable growth of MSMEs.